Mycoplasma bovis May Travel Along the Eustachian Tube to Cause Meningitis in Japanese Black Cattle. (October 2021) - Suwanruengsri, Mathurot; Uemura, Ryoko; Izzati, Uda Zahli; Kanda, Takuya; Fuke, Naoyuki; Yasuda, Masahiro; Hirai, Takuya; Yamaguchi, Ryoji
Summary: Mycoplasma bovis ( M. bovis ) is a common inhabitant of the upper and lower respiratory tracts of cattle and is considered to be the main aetiological agent of otitis media in calves. The eustachian tube appears to be the most common portal for pathogens to enter the middle ear. We investigated the transmission route of M. bovis causing otitis media that progressed to meningitis or meningoencephalitis in Japanese Black cattle. M. bovis was detected in 10 cases by a loop-mediated isothermal amplification method or by immunohistochemistry. One case of caseonecrotic granulomatous meningoencephalitis, one case of caseonecrotic granulomatous meningitis, one case of suppurative meningoencephalitis, eight cases of eustachitis, nine cases of tonsillitis and six cases of suppurative bronchopneumonia were identified by histopathological examination. M. bovis antigen was detected in the eustachian tubes of eight cases. In nine cases, M. bovis was also detected in tonsillar epithelial crypts and lumina, in intraluminal inflammatory cells and in the epithelial cells of minor salivary glands located around the eustachian tubes and tonsils. The results suggest that M. bovis can infect and colonize the tonsils and enter the eustachian tubes, causing otitis media, which, in cases of chronic infection, can progress to meningitis.